On Education-Occupation and Skill-Occupation Mismatches Among Generation Z in Egypt - Ebrahim, Hamsa Mohamed Ebrahim Yousef (AUC Knowledge Fountain, 2026)
This thesis examines the impact of education-occupation and skill-occupation mismatches, specifically with regard to Generation Z in Egypt, with a focus on prevalence, socioeconomic factors, and their impact on youth employability and human capital utilization. The research examines education and skill mismatches through a quantitative approach, relying primarily on quantitative analysis of the Egypt Labor Market Panel Survey (ELMPS) 2023 data using multinomial logistic regression for education mismatches and probit regression for skill mismatches. The results indicate that education and skill mismatches are common among employed Gen Z, with a considerable percentage of 38-45%. This is despite the fact that Egypt has a highly educated youth population and a large youth population, with 60% of the population being under 30 and approximately 21 million of that population falling within the 18-29 age bracket. Higher education levels increase over-education and over-skilling while reducing under-education, with males being more likely to experience over-education and females being more likely to experience under-education, urban dwellers being more likely to experience over-education, wealthier households reducing the likelihood of over-education and over-skilling, married individuals being more likely to experience under-education and less likely to experience over-skilling, and individuals with good soft skills, such as problem-solving and computer skills, reducing the likelihood of over-skilling. Based on the study's findings, mismatches alone indicate deeper systemic issues in the alignment of education and skills with the demands of the labor market and are not sufficiently addressed without accompanying reforms in education and job placement systems. The study's findings highlight the need to incorporate interventions targeting the development of soft skills and women to improve employability, increase youth engagement in the formal sector, and leverage the demographic dividend in Egypt, in the face of a high incidence of informal employment (around 67-68%) and a high level of youth unemployment, which often stands at 18-19% for the 15-24 age group, with even higher rates for educated youth and women. The study recommends a range of policy interventions, both short-term in the labor market, such as the establishment of a women-focused job platform by the Ministry of Manpower, and medium-term interventions in the education sector, such as the inclusion of soft skills in the curriculum by the Ministry of Education.